Macedonian Election Rules: Citizens vis-a-vis Political Parties - Bojana Naumovska, Milka Dimitrovska (Institute for Research and European Studies, 2022)
The Macedonian election rules, i.e. the setting of the electoral system, produce a double effect, an effect on the voter, and an effect on the party system. Therefore, each change in the electoral regulations would not only alter the voters’ comportment but also impact the political parties. Considering these effects, the paper aimed to compare the attitudes of the citizens and political parties regarding the electoral legislature (both for the parliamentary and local elections); and produce adequate electoral solutions as a corrective for the detected shortcomings of the current regulations. The paper relied on content analysis of theoretical literature and research, empirical qualitative research based on citizens’ focus groups from each region in Macedonia, questioned political parties, and additional data analysis. The ultimate findings propose a way to promote the equal value of each vote, proportional regional representation, and MPs' accountability at the parliamentary elections. For the local elections, the proposed solution referred to reducing the election cost, the possibility of political bargaining, and preserving the legitimacy of elected mayors.
Keywords: Electoral Regulations, Citizens, Political Parties, Parliamentary Elections, Local Elections